Genome Edited Crops Touch the Market: A View on the Global Development and Regulatory Environment - Menz, Jochen; Modrzejewski, Dominik; Hartung, Frank; Wilhelm, Ralf; Sprink, Thorben (Frontiers in Plant Science, 2020)
Products of genome editing as the most promising “New Plant Breeding Technology” (NPBT) have made the transition from the lab to the market in a short time. Globally, research activities employing genome editing are constantly expanding and more and more plants with market-oriented traits are being developed, while companies already released the first genome-edited crops to the market. Few countries, most of which are located in the Americas, have adapted legislations to these technologies or released guidelines supporting the use of genome editing. Other countries are debating the path to come either because there is no clarity on the legal classification or due consensus is hampered by a renewed GMO debate. In recent years (2017 - 2020), eight countries have introduced guidelines clarifying the legal status of genome edited products and many of those are actively committed to international harmonization of their policies. In this publication we give an overview on the current and potentially future international regulatory environment and an update on plants derived by genome editing with market oriented traits.